The Internet and the Truth about Science - Meadows, George; Howley, Aimee (Education Policy Analysis Archives, 1998)
Even though sophisticated discussion of the nature of scientific claims is taking place in the academy, public school teachers of science and mathematics may harbor naive assumptions about the way that scientific processes function to construct the "truth." Reluctant to change their prior assumptions about science, such teachers may become vulnerable to information technologies (including "low-tech" media such as textbooks and films) that construe science as a collection of facts. An on-line lesson about constructivism provided a forum in which a group of teachers revealed well-established epistemologies seemingly inimical to the principles of conceptual change teaching. Further, the strategies used by the teachers to quell a potentially interesting debate provided preliminary evidence of differences in the motives for communication in virtual, in contrast to real, communities.